2009
DOI: 10.1055/s-0029-1185505
|View full text |Cite
|
Sign up to set email alerts
|

Carboline Alkaloids fromTrigonostemon lii

Abstract: Three types with six new carboline alkaloids, trigonostemonines A-F (1- 6), were isolated from the roots and stems of Trigonostemon lii. Their structures were elucidated by spectroscopic analyses. It is the first time that beta-carboline alkaloids have been reported in Trigonostemon species. Trigonostemonine F (6) exhibited moderate cytotoxic activity against HL-60 with an IC (50) value of 16 microM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…The spectroscopic data of compound 6 were similar to trigonostemonine E. 21 Comparison of the 1 H and 13 C NMR data (Tables 2 and 3) with those of trigonostemonine E revealed that compound 6 had a similar 1-(quinolinyl)-3,4-dihydro- β -carboline skeleton. Unlike trigonostemonine E, the O -methyl group was located at C-9.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…The spectroscopic data of compound 6 were similar to trigonostemonine E. 21 Comparison of the 1 H and 13 C NMR data (Tables 2 and 3) with those of trigonostemonine E revealed that compound 6 had a similar 1-(quinolinyl)-3,4-dihydro- β -carboline skeleton. Unlike trigonostemonine E, the O -methyl group was located at C-9.…”
Section: Resultsmentioning
confidence: 70%
“…Pegaharmine G ( 6 ) was isolated as a yellow, amorphous powder, and its molecular formula was determined as C 21 H 17 N 3 O based on a positive HRESIMS ion at m / z 328.1440 [M + H] + (calcd for 328.1444). The spectroscopic data of compound 6 were similar to trigonostemonine E . Comparison of the 1 H and 13 C NMR data (Tables and ) with those of trigonostemonine E revealed that compound 6 had a similar 1-(quinolinyl)-3,4-dihydro-β-carboline skeleton.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the presence of regioisomeric pairs is commonly observed in the trigonostemon alkaloids family (Figure 1). 37 Hence, we reasoned that the formation of both regioisomers during the oxidation of bistryptamine precursor might explain the biodiversity observed in the trigonostemon alkaloids family. Notably, modification of bistryptamine 32 through an N1-protection with various electron withdrawing groups greatly altered their chemical properties toward oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, simple exposure of bistryptamine 16 to air over 12 days resulted in autoxidation to (±)-hydroxyindolenines 17 and 18 ( 17:18 = 1.5:1) in 27% yield along with recovered 16 (65%). Interestingly, the presence of regioisomeric pairs is commonly observed in the trigonostemon alkaloids family 15 (Figure 1) and the major autoxidation product (oxidation of 6-methoxy-indole substructure) is consistent with the major isolated trigonoliimines A ( 1 ) and C ( 3 ). 1 Given the rapid oxidation of bistryptamine 16 , and based on observations on stereoselective oxidation of related derivatives, 4,5,7,16 we focused our attention on the use of oxaziridines.…”
mentioning
confidence: 82%